1996
DOI: 10.1161/01.str.27.2.290
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Extracranial Vertebral Artery Dissection With Duplex Color-Flow Imaging

Abstract: Extracranial vertebral artery dissections can be diagnosed noninvasively with duplex color-flow imaging. It is therefore a useful method for early diagnosis and follow-up examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 27 publications
2
55
0
4
Order By: Relevance
“…VAD characteristics. In the larger study on the topic, where 15 patients have been enrolled [15], a dissection was primarily detect with duplex color-flow imaging. In these patients the interval between the initial clinical symptoms and ultrasound examination was 2-3 days (range 0.5-4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VAD characteristics. In the larger study on the topic, where 15 patients have been enrolled [15], a dissection was primarily detect with duplex color-flow imaging. In these patients the interval between the initial clinical symptoms and ultrasound examination was 2-3 days (range 0.5-4).…”
Section: Discussionmentioning
confidence: 99%
“…Color-Doppler sonography, which is a non-invasive and costeffective method, is a suitable screening test for vertebral artery stenosis and dissection [15][16][17]. However, very few studies have been performed to determine Doppler criteria for identifying proximal vertebral artery stenosis [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…10 The use of ultrasonographic techniques in the initial assessment of patients with suspected dissection has invariably required confirmatory testing with additional angiography, either invasively or noninvasively. The technique is dependent on the accessibility of the region to screening and although helpful for proximal dissections, the detection of more distal disease is limited 11,12 Controversy continues as to the optimal management of patients with asymptomatic vertebral artery injury. Guidelines published in 2002 indicated that there was insufficient evidence to support anticoagulation in asymptomatic patients, specifically relating to a 14% risk of complications from anticoagulant use.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, 12.5% of the screws were considered critical. No alterations to perfusion of the vertebral artery as evaluated by duplex color-flow imaging, which has been proven as a reliable diagnostic tool for the assessment of vertebral artery lesions [3,4], have been detected. None of the malpositioned screw led to clinical symptoms and had to be revised (Group 3).…”
Section: Accuracy Of Pedicle Screw Positionmentioning
confidence: 99%